Kemampuan Mengenal Huruf Hijaiyah Melalui Media Kartu Bergambar - Hasan Syahrizal; Sukarno Sukarno; Abdul Muntholib (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Improper use of media in introducing arabic alphabets becomes one of the triggers for chldren’s difficulties in recognizing Arabic alphabets which have similarities in form but they are different in pronunciation. They will impact much to children recitation of holy Qur’an. This study aims at supporting media of picture card for introduction of Arabic alphabets to children. The study provided description of the process of introducing Arabic alphabets from several studies related to media of picture card for introducing Arabic alphabets. It also provided activities of introducing Arabic alphabets from the first step to the last of the study. The descriptions provided are about aspects to introducing Arabic alphabets such as pronunciation, pointing out, and distinguishing.